Perpetrators of Genocide: An Explanatory Model of Extraordinary Human Evil - James Waller (Journal of Hate Studies, 2002)
According to Jewish-Christian tradition, the first time that death appeared in the world, it was murder. Cain slew Abel. Two men, says Elie Wiesel, and one of them became a killer.1 Throughout human history, social conflict is ubiquitous. Wars erupt naturally everywhere humans are present. Since the Napoleonic Wars, we have fought an average of six international wars and six civil wars per decade. The four decades after the end of World War II saw 150 wars and only 26 days of world peaceand that does not even include the innumerable internal wars and police actions. Buried in the midst of all of our progress in the twentieth century are well over a hundred million persons who met a violent death at the hands of their fellow human beings. That is over five times the number from the nineteenth century and more than ten times the number from the eighteenth century.2